2015
DOI: 10.1049/iet-est.2014.0045
|View full text |Cite
|
Sign up to set email alerts
|

Single‐phase rectifier circuit with output voltage enhancement for automotive generators

Abstract: This study presents a new concept for single-phase diode bridge rectifier circuits applied to automotive applications. The proposed circuit is able to enhance the output voltage to a much higher output level over a wide load range compared to the classical single-phase diode bridge rectifier without using complex control algorithms. This is achieved by embedding two capacitors and two switches to a new designed diode bridge converter topology. The embedded capacitors are charged and discharged simultaneously w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Next step is to implement an effective monitoring technique which generally depends on two essential aspects [27]: Various innovative monitoring techniques have been proposed to capture and indicate the electrical parameters of electrolytic capacitors in real-time [7,14,23,24,[28][29][30]. Most of these methods are based on ESR estimation which can be implemented through two main approaches [31,32]: † ESR = (V CRMS /I CRMS ), where V CRMS and I CRMS are the RMS voltage and RMS current of capacitor, respectively. † ESR = P C /I 2 CRMS , where P C and I CRMS are the average dissipated power and RMS current of capacitor, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next step is to implement an effective monitoring technique which generally depends on two essential aspects [27]: Various innovative monitoring techniques have been proposed to capture and indicate the electrical parameters of electrolytic capacitors in real-time [7,14,23,24,[28][29][30]. Most of these methods are based on ESR estimation which can be implemented through two main approaches [31,32]: † ESR = (V CRMS /I CRMS ), where V CRMS and I CRMS are the RMS voltage and RMS current of capacitor, respectively. † ESR = P C /I 2 CRMS , where P C and I CRMS are the average dissipated power and RMS current of capacitor, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Next step is to implement an effective monitoring technique which generally depends on two essential aspects [27]: Capturing and indicating the real‐time electrical parameters of capacitor including ESR and/or capacitance. Predicting the EOL of the component for preventive maintenance. Various innovative monitoring techniques have been proposed to capture and indicate the electrical parameters of electrolytic capacitors in real‐time [7, 14, 23, 24, 28–30]. Most of these methods are based on ESR estimation which can be implemented through two main approaches [31, 32]: ESR = ( V CRMS / I CRMS ), where V CRMS and I CRMS are the RMS voltage and RMS current of capacitor, respectively. ESR=)(PC/IC2RMS, where P C and I CRMS are the average dissipated power and RMS current of capacitor, respectively. These two general approaches have been compared and discussed in [32]. Since the real‐time ESR estimation technique is out of the scope of this research, more details regarding this topic can be found in the introduced references.…”
Section: Introductionmentioning
confidence: 99%